2016
DOI: 10.1093/jxb/erw268
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of vascular and extra-vascular water pathways to drought-induced decline of leaf hydraulic conductance

Abstract: Drought stress can impair leaf hydraulic conductance (Kleaf), but the relative contribution of changes in the efficiency of the vein xylem water pathway and in the mesophyll route outside the xylem in driving the decline of Kleaf is still debated. We report direct measurements of dehydration-induced changes in the hydraulic resistance (R=1/K) of whole leaf (Rleaf), as well as of the leaf xylem (Rx) and extra-vascular pathways (Rox) in four Angiosperm species. Rleaf, Rx, and Rox were measured using the vacuum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 59 publications
5
83
0
Order By: Relevance
“…For many species, K leaf in hydrated leaves can be enhanced by many fold under high irradiance likely due to aquaporin expression (Cochard et al, 2007;Scoffoni et al, 2008;Maurel et al, 2015) and such high-light-acclimated leaves show stronger vulnerability before the turgor loss point (Guyot et al, 2012;Sack et al, 2016b). Similarly, a recent study partitioning the vulnerabilities of K x and K ox found that K ox was the strongest determinant of K leaf decline in two of four species (Trifiló et al, 2016), and, for the other two species, both xylem and outsidexylem pathways appeared to be strong drivers of K leaf decline. However, hydraulics measurements were performed in that study under low light, likely minimizing the response of K ox before the turgor loss point.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…For many species, K leaf in hydrated leaves can be enhanced by many fold under high irradiance likely due to aquaporin expression (Cochard et al, 2007;Scoffoni et al, 2008;Maurel et al, 2015) and such high-light-acclimated leaves show stronger vulnerability before the turgor loss point (Guyot et al, 2012;Sack et al, 2016b). Similarly, a recent study partitioning the vulnerabilities of K x and K ox found that K ox was the strongest determinant of K leaf decline in two of four species (Trifiló et al, 2016), and, for the other two species, both xylem and outsidexylem pathways appeared to be strong drivers of K leaf decline. However, hydraulics measurements were performed in that study under low light, likely minimizing the response of K ox before the turgor loss point.…”
Section: Resultsmentioning
confidence: 91%
“…However, there has been a lack of information of the number of embolized xylem conduits within given vein orders across the range of leaf water stress and their influence on K leaf (Wylie, 1947;McKown et al, 2010;Sack and Scoffoni, 2013) relative to the potentially strong role of vulnerability of the outside-xylem pathways. Recent work has proposed that outside-xylem hydraulic decline may play a role in K leaf decline (Sade et al, 2014;Scoffoni et al, 2014;HernandezSantana et al, 2016;Trifiló et al, 2016). A study that partitioned the vulnerability of K leaf into that of K x and K ox (Trifiló et al, 2016) found that both contributed, depending on species, but measurements were made under low irradiance, which would minimize the response of K ox before the turgor loss point (Guyot et al, 2012;Sack et al, 2016b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies further showed that K leaf is responsive to internal and external factors that affect both xylem and living tissues, such as temperature, light and water status. In this issue, Trifiló et al (2016) extend the dissection approach to clarify the response of K leaf to dehydration.…”
mentioning
confidence: 99%
“…The mechanisms underlying stomatal sensitivity to VPD remain a controversial and active area of research, with the possibility of liquidand/or vapor-phase signals being involved alongside ABA synthesis and signaling within guard cells (Peak and Mott, 2011;Bauer et al, 2013;Buckley and Mott, 2013;Mott and Peak, 2013;McAdam et al, 2016). Because of the potentially significant metabolic and signaling interactions between guard cells and the mesophyll, integrated investigation of stomatal sensitivity and the dynamic responses of the critical extravascular component of leaf hydraulic conductance in CAM (and C 3 ) species is highly desirable Trifiló et al, 2016). Analysis of the spatiotemporally dynamic expression patterns of aquaporins and of possible interactions between stomatal physiology and mesophyll osmotic properties could be especially fruitful (Pou et al, 2013;Martorell et al, 2015).…”
Section: Stomatal Responses To External Stimulimentioning
confidence: 99%